Can a virtual environment enhance understanding of hoarding deficits? A pilot investigation - Yasara Nayanthara Somaratne (Elsevier, 2021)
This pilot study tested the utility of a virtual environment for assessing cognitive deficits characteristic of hoarding. A sample representing a broad spectrum of hoarding traits (N = 20) was assessed using self-report measures of information processing skills and emotional experience, and placed in a virtually simulated house that contained cluttered spaces and clean spaces. Information-processing significantly differed between high-hoarding and low-hoarding groups, with the high-hoarding group showing increased proneness to emotional attachment and information processing difficulties in the cluttered environment. The high-hoarding group also showed differences in behaviour and appraisal of the simulated environment. The findings suggested that virtual reality is accessible to participants and elicits real-time emotions and behavioural parameters which can assist our understanding of hoarding behaviour. Virtual reality may contribute to hoarding therapy in future, as it allows participants to visualise a different perspective of their condition and could contribute to their knowledge about the severity of their behaviour.